2008
DOI: 10.1111/j.1540-8159.2008.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Effects of Endocardial and Epicardial Percutaneous Radiofrequency Catheter Ablation in Dilated Nonischemic Cardiomyopathy

Abstract: We report the histological evaluation of both endocardial and epicardial radiofrequency (RF) ablation lesions in the explanted heart of a patient presenting with nonischemic dilated cardiomyopathy complicated by recurrent electrical storms. In this case, chronic RF lesions were almost transmural at the endocardial side, while remaining only superficial at the epicardial aspect, possibly because of the insulating interposed epicardial fat layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The distribution of the substrate for VT depends on its etiology, with development of a VT substrate on the epicardial surface being common in nonischemic cardiomyopathy. 20,33,34 On the other hand, ischemic cardiomyopathy is frequently associated with dysfunctional and heterogeneous endocardial conduction, while the need for epicardial access to treat VT is less frequent. 12,13 Several authors have reported reduction of the endocardial unipolar voltage in animal models of chronic infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the substrate for VT depends on its etiology, with development of a VT substrate on the epicardial surface being common in nonischemic cardiomyopathy. 20,33,34 On the other hand, ischemic cardiomyopathy is frequently associated with dysfunctional and heterogeneous endocardial conduction, while the need for epicardial access to treat VT is less frequent. 12,13 Several authors have reported reduction of the endocardial unipolar voltage in animal models of chronic infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In past years, it has become clear that both endocardial and epicardial approaches may be required for an effective treatment of ventricular tachycardia (VT) in patients with nonischemic left-and right-side cardiomyopathy [2][3][4][5] and sometimes in VTs occurring after myocardial infarction. 6 -9 Clinical Perspective on p 659…”
mentioning
confidence: 99%
“…This case represents a successful RF ablation of a monomorphic VT electrical storm in a patient with NIDCM. In NIDCM, the ventricular myocardium was shown to contain multiple patchy areas with replacement by fibrosis either intramural or extended to the epicardium and/or the endocardium of the left and right ventricles in a previous gross histological study 1,2 . In this case, the activation sequence of VT‐2 conducted from the apex to the lateral wall and septum of the RV epicardium during the diastolic period of the VT (RV‐VT).…”
Section: Discussionmentioning
confidence: 95%
“…Sustained monomorphic ventricular tachycardia (VT) in patients with nonischemic dilated cardiomyopathy (NIDCM) is relatively uncommon in comparison to VTs associated with a prior myocardial infarction (MI). Catheter ablation of VTs due to myocardial reentry in NIDCM is generally thought to be more difficult than that in patients with an MI because of its specific patchy fibrosis and abnormal conduction patterns 1–2 . Previous reports demonstrated that epicardial ablation was effective for myocardial reentrant VT in some cases 3–4 .…”
Section: Introductionmentioning
confidence: 99%